A comparison of mRNA and circRNA expression between squamous cell carcinoma and adenocarcinoma of the lungs - Min Yu; Yingxuan Tian; Min Wu; Jinglong Gao; Yuan Wang; Fuqiang Liu; Sen Sheng; Shufen Huo; Jun Bai (Genetics and Molecular Biology, 2020)
Abstract Lung squamous cell carcinoma (LUSC) and lung adenocarcinoma (LUAD) are the two major subtypes of non–small-cell lung cancer (NSCLC). This study aimed to compare mRNA and circRNA expression patterns between LUSC and LUAD. Cancer tissues from 8 LUSC patients and 12 LUAD patients were collected to obtain mRNA and circRNA expression profiles. The differentially expressed mRNAs (DEmRNAs) and circRNAs (DE-circRNAs) between LUSC and LUAD were screened. Afterwards, miRNA–DEcircRNA pairs and miRNA–DEmRNA pairs were predicted to construct a competing endogenous RNAs (ceRNAs) network, followed by functional enrichment analysis and survival analysis. In total, 635 DEmRNAs and 245 DEcircRNAs were obtained. The ceRNA analysis revealed that genes, such as EPHA2, EPHA7, NTRK2, CDK6, hsa_circ_027570, hsa_circ_006089, and hsa-circ_035997, had distinct expression patterns between LUSC and LUAD. Also, functional enrichment analysis indicated that DEmRNAs were mainly enriched in ERK1 and ERK2 cascade. Survival analyses suggested that STXBP1 and PMEPA1 were associated the prognosis of with both LUAD and LUSC, whereas EPHA2 and CDK6 might serve as prognostic factors for LUSC and LUAD, respectively. In conclusion, genes such as EPHA2, EPHA7, NTRK2, and CDK6 had different patterns in the two major histological subtypes of NSCLC. Notably, EPHA2 and CDK6 might be considered as potential therapeutic targets for LUSC and LUAD, respectively.